Impact of Social Media on B2B Sales - Fischer, Marek (2018)
This diploma thesis focuses on social media usage in B2B sales. Based on the systematic literature review conducted by the author, he has found out that recent researchers (Salo, 2017) suggest further research in the area of how and in which sales phase should various social networking sites, technologies and plugins used. To further fill this research gap, author decided to identify these social media and their usage among B2B salespeople in the so-called social selling process. The social selling process in this thesis applies mainly to acquiring new prospects and tangentially to taking care of existing clients (follow-up step). Author has chosen a qualitative research method via conducting 10 in-depth semi-structured interviews to reveal these instruments as well as motivation of a sales person on why to use social media in the selling process. The collected data was analyzed using Thematic analysis to ensure the right procedure and to identify main themes which crystalized into 2 main strategic approaches in social selling. These approaches (Push and Pull) include practical examples of concrete activities which sales people can use in their daily jobs and are presented with focus on practicality and ease of implementation. These also form the main contribution of author`s research. In the last part, author mentions challenges in social selling and recommended managerial implications for salesforce.